Circuits Regulating Pleasure and Happiness in Bipolar Disorder - Loonen, Anton J. M.; Kupka, Ralph W.; Ivanova, Svetlana A. (Frontiers in Neural Circuits, 2017)
According to our model, the motivation for appetitive-searching versus distress-avoiding behaviors is regulated by two parallel cortico-striato-thalamo-cortical re-entry circuits that include the core and the shell parts of the nucleus accumbens, respectively. An entire series of basal ganglia, running from the caudate nucleus on one side to the centromedial amygdala on the other side, control the intensity of these reward-seeking and misery-fleeing behaviors by stimulating the activity of the (pre)frontal and limbic cortices. Hyperactive motivation to display behavior that potentially results in reward induces feelings of hankering (relief leads to pleasure); while, hyperactive motivation to exhibit behavior related to avoidance of misery results in dysphoria (relief leads to happiness). These two systems collaborate in a reciprocal fashion. We hypothesized that the mechanism inducing the switch from bipolar depression to mania is the most essential characteristic of bipolar disorder. This switch is attributed to a dysfunction of the lateral habenula, which regulates the activity of midbrain centers, including the dopaminergic ventral tegmental area. From an evolutionary perspective, the activity of the lateral habenula should be regulated by the human homologue of the habenula-projecting globus pallidus, which in turn might be directed by the amygdaloid complex and the phylogenetically old part of the limbic cortex. In bipolar disorder, it is possible that the system regulating the activity of this reward-driven behavior is damaged or the interaction between the medial and lateral habenula may be dysfunctional. This may lead to an adverse coupling between the activities of the misery-fleeing and reward-seeking circuits, which results in independently varying activities.